NALISIS KINERJA KERUSAKAN JALAN (RIGID PAVEMENT) PADA RUAS JALAN JAKENAN WINONG KABUPATEN PATI - Rifan, Moh Moh (Jurnal Pengembangan Rekayasa dan Teknologi, 2022)
The Jakenan-Winong road is a regional link between the Jakenan area and the cities of Pati and Juwana. Due to the high mobilization of vehicles due to the repair of the Pati Rembang road on this road section, not a few damage to the concrete surface (rigid pavement) has occurred, one of the causes of which is the overload of large vehicles. From the known problems, this research was conducted to identify whether the damage that occurred could affect road performance on that road section. Data analysis used the 1997 Indonesian Road Capacity Manual (MKJI) method to determine traffic performance. From the research results, it can be seen the level of road performance on Jakenan Winong streat, Pati City during morning peak hours, noon peak hours, and evening peak hours, the level of service is in category B.  From the research results it can also be seen that the damage that occurred on the Jakenan -Winong road section did not affect the level of road performance.
Keywords: Road Performance; Rigid Pavement; Overloaded Vehicles; Road Damage.